Feasibility of a streamlined imaging protocol in technetium-99m-Tektrotyd somatostatin receptor SPECT/CT. Issue 6 (June 2018) - Al-Chalabi, H.; Cook, A.; Ellis, C.; Patel, C.N.; Scarsbrook, A.F.
Abstract : Aim: To assess the feasibility and efficacy of a streamlined single time-point 99m Tc-HYNIC-Tyr3-octreotide (Tektrotyd) somatostatin receptor scintigraphy (SRS) protocol to differentiate pathological uptake by neuroendocrine tumours (NETs) from physiological activity. Methods and materials: Tektrotyd imaging in 50 consecutive patients with NETs was reviewed retrospectively. Imaging was independently assessed by two experienced reporters with dual-certification in radiology and nuclear medicine and agreed in consensus. The presence of physiological bowel activity and/or further sites of equivocal uptake on 4-hour planar imaging and whether combined single-photon-emission computed tomography (SPECT)/computed tomography (CT) assessment allowed accurate diagnosis was tabulated. A judgement was also made in each case on whether 2-hour planar imaging was necessary for accurate diagnostic interpretation. Results: Thirty-six patients (72%) had positive findings on Tektrotyd SPECT/CT. Eight patients (16%) had bowel activity on 4-hour planar imaging, which could be considered to have hampered interpretation without access to SPECT/CT. Eleven studies in 10 patients (20%) demonstrated areas of indeterminate uptake on planar imaging; five in the uncinate process of the pancreas, three in the nasal cavity or paranasal sinuses, one in the adrenal glands, one in a focus of inflammation on the posterior abdominal wall, and one at the tip of a central venous line. In all cases, accurate interpretation of findings was possible with SPECT/CT, without the 2-hour planar image. Conclusion: Two-hour planar imaging could be safely omitted from Tektrotyd SRS incorporating SPECT/CT imaging without reducing the accuracy of diagnostic interpretation. Streamlined imaging has the potential to reduce patient inconvenience and improve scanner and staff efficiency. Highlights: SPECT/CT improves accuracy of somatostatin receptor scintigraphy (SRS). A single time-point Tektrotyd SRS protocol has the potential to improve efficiency. 2-hour planar imaging could be safely omitted from Tektrotyd SRS including SPECT/CT.